Unconventional monetary policies in the eurozone and the provision of credit: an events study approach - Batista, Joana Bárbara Monteiro (2017)
In order to achieve low and stable inflation rates, the European Central Bank (ECB) usually used conventional monetary instruments. However, the financial crisis brought some challenges to these traditional instruments since the goal was to stimulate the economy in a scenario of very low inflation. In the aftermath of the financial crisis, the policy interest rate in many developed economies reached the Zero Lower Bound due to low inflation and conventional monetary policies started to be ineffective to stimulate economic growth. As a consequence of the crisis, unconventional monetary policies started to be implemented in the World most important economies, namely in the USA, the UK and the Euro Area. Using an Events Study Method we study how the European credit market responds to these unconventional monetary policies implemented by the ECB in the period between 2008 and 2016. Our results suggest that both the monthly net purchase of Public Sector Purchase Program and the dummy associated to the events study method of unconventional monetary policy, have a positive impact in the different kind of credit concession.